Aristotle and Diogenes the Cynic - Brancacci, Aldo (Peitho. Examina Antiqua, 2020)
In this paper I examine the testimonium of Aristotle’s Rhetoric concerning Diogenes the Cynic (SSR V B 184). This piece of evidence is the most ancient source of Diogenes and proves that Aristotle was familiar with his writings. I also study the testimonium on Diogenes that is handed down by Theophrastus (SSR V B 172), which confirms the interest of the ancient Peripatos in this philosopher. Finally, I examine a passage of Book 1 of the Politics where Aristotle refers to the thesis on the abolition of money. I argue that such a thesis could be ascribed to Diogenes. In particular, I attempt to demonstrate that several theses of political philosophy put forward by Diogenes should be considered as constituting a polemical overthrow of the corresponding theses of Aristotle in Book 1 of his Politics.